2023
DOI: 10.3390/su15129358
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Financial Literacy: A Systematic Literature Review of Determinants and Recent Trends

Azra Zaimovic,
Anes Torlakovic,
Almira Arnaut-Berilo
et al.

Abstract: Financial literacy is a critical life skill that is essential for achieving financial security and individual well-being, economic growth and overall sustainable development. Based on the analysis of research on financial literacy, we aim to provide a balance sheet of current research and a starting point for future research with the focus on identifying significant predictors of financial literacy, as well as variables that are affected by financial literacy. The main methods of our research are a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 209 publications
0
9
0
Order By: Relevance
“…In choosing appropriate and standardized keywords, for some terms, we inspired ourselves with the conceptual framework and keywords proposed by Zaimovic et al [5] and shown in Figure 3. 2 Vosviewer has the option "All keywords" but in our unified dataset it would have not solved the problem Additionally, for duplicate records, the automatic keywords (Keyword Plus or Index Keywords) differ in many cases due to the specific algorithms used by the database's providers.…”
Section: The Software and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In choosing appropriate and standardized keywords, for some terms, we inspired ourselves with the conceptual framework and keywords proposed by Zaimovic et al [5] and shown in Figure 3. 2 Vosviewer has the option "All keywords" but in our unified dataset it would have not solved the problem Additionally, for duplicate records, the automatic keywords (Keyword Plus or Index Keywords) differ in many cases due to the specific algorithms used by the database's providers.…”
Section: The Software and Methodologymentioning
confidence: 99%
“…They provide maps of the state of the art in a given area of scientific knowledge, and they help identify different structures within a research field, hot topics and evolving research frontiers. These tools have been recently used in the domain of financial literacy [1][2][3][4][5] or in specific financial domains such as banking [6,7], insurance [8], Islamic insurance [9], consumer credit [2], ITC and financial education [10] and green finance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unsustainable farming practices and environmental pollution have contributed to climate change and a worsening performance of the farming sector in many countries [17,18,37]. In fact, several regions are experiencing water shortages due to various reasons, including water overuse, competition for water, and decreased rainfall caused by climate change [7,38].…”
Section: Smart Farming Technologiesmentioning
confidence: 99%
“…In developing countries, such as Algeria, many farmers still use inefficient and unsustainable farming methods. The adoption of innovative technologies remains a challenging issue [17,18]. Although the Algerian government has made efforts to develop the agriculture sector and achieve sustainability in energy and water use [19], efforts to promote sustainable practices among farmers, particularly in the area of water conservation, require further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Botelho (2022) [62] demonstrate that advanced financial literacy has a positive impact on the decisions that individuals make regarding sustainable finance investments. Zaimovic et al (2023) [63] underline that enhancing financial literacy contributes to an increase in sustainable investments by individuals and the attainment of sustainable development goals. Beny et al (2023) [64] unveil that financial literacy holds significant importance for individuals in adopting sustainable and innovative practices.…”
Section: Sustainable Finance Literacymentioning
confidence: 99%